A glimpse into Dave Wagner`s training regimen - Lawson, E. (Olympic & Paralympic Coach, 2013)
David Wagner is the United States` most decorated wheelchair tennis athlete. Wagner already has six Paralympic medals to his credit, including three consecutive golds in quad doubles. Individually, Wagner claimed the silver medal at both the Athens and London Games, along with the bronze medal at the Beijing Games. Wagner competes in the quadriplegic open division as sanctioned and regulated by the International Tennis Federation. He sustained a cervical spine injury several years ago and has virtually no sensation or voluntary muscular activity below high torso. He has use of his arms with very limited grip ability in both hands. He must painstakingly tape his tennis racket to his right hand for every practice and match. Prior to his injury, Wagner played one year of community college tennis and was also an accomplished high school basketball player. The wheelchair tennis circuit, for the most part, follows the able-bodied ATP schedule, with tournament play beginning in January and running through November. The offseason runs from mid-November through December. During his offseason, Wagner spends four to six hours per day on the tennis court, breaking his time up into different training segments. On-court time consists of specific tennis court drills, match play and pushing (conditioning drills in the chair that are analogous to able-bodied foot work drills). Every other day, in addition to the court work, Wagner spends 30 to 45 minutes in the weight room performing a mixture of core exercises, conditioning, and weight training exercises. The major objectives of the off-court training are to maintain or improve play stamina, decrease severity and incidence of injury, optimize recovery, and improve pushing power. Wagner has a menu of seven different workouts from which to choose on any given day.